PENGARUH PEMAHAMAN MUZAKKI TENTANG ‎MANFAAT ZAKAT ‎MAAL BAGI PRODUKTIVITAS ‎EKONOMI PARA MUSTAHIQ ‎TERHADAP KEPEDULIAN ‎SOSIAL DAN KEPATUHAN MEMBAYAR ‎ZAKAT ‎ ‎( Studi Khusus Masyarakat Desa Burneh Bangkalan )‎ - Hisbullah; Sholeh, Badrus; Mashudi (Wasīlah: Journal Of Sharia Sciences, 2026)
This study aims to analyze the effect of muzakki’s understanding of the benefits of zakat maal on social concern and compliance in paying zakat. The research employs a quantitative approach using a survey method by distributing questionnaires to 97 respondents in Burneh Village, Bangkalan. Data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results indicate that muzakki’s understanding has a positive and significant effect on both social concern and zakat payment compliance, either partially or simultaneously. These findings suggest that a better understanding of zakat benefits, particularly in improving the economic productivity of mustahiq, can enhance social awareness and compliance behavior. Furthermore, the study highlights that muzakki’s understanding serves as a key factor linking cognitive, social, and behavioral aspects in zakat practices. This research provides important implications for zakat management institutions to strengthen educational and socialization strategies in order to optimize zakat collection and reinforce its role as an instrument for community economic empowerment.